2019
DOI: 10.1097/rhu.0000000000001218
|View full text |Cite
|
Sign up to set email alerts
|

Periarticular Neurofascial Dextrose Prolotherapy Versus Physiotherapy for the Treatment of Chronic Rotator Cuff Tendinopathy

Abstract: Background/Objective: Rotator cuff tendinopathy is a common cause of shoulder pain. We aimed to compare periarticular (neurofascial) dextrose prolotherapy versus physiotherapy for treatment of chronic rotator cuff tendinopathy in the short term. Methods:We carried out a randomized clinical trial with 2 arms at a university hospital. In total, 66 patients with chronic rotator cuff tendinopathy, proven by magnetic resonance imaging, were randomly allocated to 2 groups. The outcomes were change in shoulder pain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…8,11,12 In addition, prolotherapy, botulinum toxin, and platelet-rich plasma have been reported to yield better outcomes in patients with shoulder pain. [13][14][15][16] Recently published systematic reviews and guidelines indicated that surgery does not provide notable improvements in pain, function, or quality of life (QOL) compared with PT. 17,18 Hyaluronic acid (HA) is a major glycosaminoglycan of the extracellular matrix.…”
mentioning
confidence: 99%
“…8,11,12 In addition, prolotherapy, botulinum toxin, and platelet-rich plasma have been reported to yield better outcomes in patients with shoulder pain. [13][14][15][16] Recently published systematic reviews and guidelines indicated that surgery does not provide notable improvements in pain, function, or quality of life (QOL) compared with PT. 17,18 Hyaluronic acid (HA) is a major glycosaminoglycan of the extracellular matrix.…”
mentioning
confidence: 99%
“…The majority of included studies were from Europe (21.40.38%) and the remaining from Asia, (18, 34.6%), South America (5 (9.62%), North America (4,7.69%), and Australia (4 (7.69%). 22 out 52 studies had published protocols available [ 32 , 33 , 36 , 37 , 40 , 43 , 44 , 47 , 53 , 58 , 61 , 65 , 68 , 69 , 71 , 72 , 74 76 , 78 , 80 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…ER ROM had 12 studies with high risk [ 34 , 38 , 39 , 41 , 48 , 57 , 59 , 62 , 70 , 75 , 81 , 84 ] and 5 with some concerns [ 35 , 40 , 56 , 63 , 77 ]. SPADI consisted of 8 studies at high risk [ 32 , 38 , 43 , 59 , 75 , 76 , 83 , 84 ], 13 with some concerns [ 35 , 42 , 51 , 52 , 60 , 61 , 65 , 67 , 72 , 80 , 82 , 85 , 86 ] and 3 with low risk of bias [ 69 , 73 , 74 ]. Finally, DASH had 8 studies at high risk [ 32 , 34 , 47 , 50 , 66 , 70 , 79 , 81 ], 7 with some concerns [ 33 , 36 , 37 , 44 ,…”
Section: Resultsmentioning
confidence: 99%
“…7,8 Some medications, including corticosteroids, nonsteroidal anti-inflammatory drugs, hyaluronic acid (HA), botulinum toxin, platelet-rich plasma, and dextrose, have been used for injection therapy of rotator cuff tendinopathy. 2,3,9 However, few studies have been carried out to compare the efficacy and toxicity of these medications. 2 Therefore, choosing among different injection substances in rotator cuff tendinopathy is still an open subject of research.…”
Section: Introductionmentioning
confidence: 99%